Genetic and clinical insights into MAST4-related neurodevelopmental disorders - Zheng, Xiaohong; Fan, Foyang; Lei, Bin; Xu, Yao; Peng, Min; Zhou, Youfeng (Frontiers in Pediatrics, 2025)
ObjectiveDe novo variants in MAST4 are increasingly implicated in neurodevelopmental disorders (NDDs), but the associated phenotypic spectrum remains incompletely characterized. We report a Chinese child with global developmental delay (GDD) and a novel MAST4 variant, further delineating the genotype-phenotype correlations for this gene.MethodsClinical and genetic data were retrospectively analyzed for a proband diagnosed with a MAST4-related NDD at Fujian Children's Hospital. Trio-based whole-exome sequencing (WES) and subsequent Sanger sequencing were performed to identify and validate the pathogenic variant.ResultsThe 4-year-old male proband exhibited GDD with intellectual, motor, and speech impairments. Brain MRI showed delayed myelination. WES revealed a heterozygous MAST4 missense variant (NM_001164664.2: c.4142G>T, p.Arg1381Leu), absent in population databases (gnomAD) and confirmed as de novo. The variant affects a highly conserved residue, supporting its likely pathogenicity. Phenotypic comparison with five previously reported cases confirmed core features of GDD and white matter abnormalities, though our patient lacked infantile spasms, underscoring clinical heterogeneity.ConclusionThis study reinforces MAST4's role in NDDs and expands the genetic and phenotypic spectrum associated with this gene. The absence of infantile spasms in our case suggests variable expressivity, necessitating further functional studies to assess the variant's pathogenicity and MAST4's neurobiological mechanisms.